Gender Equality in the Distribution of Inheritance Property from Al-Qur'an and Mawaris Fiqh’s Perspective - Safitri, Hani Hasnah; Khumaedy, Agus (Prodi Hukum Ekonomi Syariah (Muamalah), 2024)
Inheritance is the transfer of assets or transfer of ownership rights from someone who has died to then be given to the rightful heirs. From the perspective of Islamic law, boys have greater inheritance rights than girls. This caused controversy among feminists who considered differences in the distribution of inheritance as unfair under the pretext of gender equality and women's emancipation. This study aims to determine the perspective of the Qur'an and Islamic fiqh regarding gender equality in the distribution of inheritance. By using a literature study research method, this article shows that; 1) From the perspective of the Al-Qur'an, Surah An-Nisa verse 11, the distribution of inheritance to boys and girls is unequal because boys get a 2:1 share from girls. 2) In the perspective of the Maharis fiqh regarding gender equality in the 2:1 division of inheritance between boys and girls, it is associated with proportional rights and obligations between the two, men's greater burden and obligation to provide for the family and parents after marriage.